1997
DOI: 10.1002/(sici)1097-0142(19970401)79:7<1401::aid-cncr18>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Soluble interleukin-2 receptor serum level as a predictor of locoregional control and survival for patients with head and neck carcinoma

Abstract: This study shows that serum s-IL-2-R level at the time of diagnosis represents a new independent prognostic variable for predicting the risk of locoregional recurrence and survival for patients with head and neck squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
3
7
0
2
Order By: Relevance
“…This experience is in accordance with previous reports linking elevated IL-6 levels to extensive disease [20], and more specifically, to lymph node involvement [26]. It is not surprising since this multifunctional cytokine plays an important role in promoting tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
“…This experience is in accordance with previous reports linking elevated IL-6 levels to extensive disease [20], and more specifically, to lymph node involvement [26]. It is not surprising since this multifunctional cytokine plays an important role in promoting tumorigenesis.…”
Section: Discussionsupporting
confidence: 92%
“…[8], [38], [39], [40] However, few studies have investigated the role of CRP in PLC. (Table S1) [38], [41], [42], [43], [44] The current study, which includes the largest number of patients, demonstrated that an elevated CRP level was associated with clinical tumor status (P = 0.005), clinical nodal status (P = 0.003) and differentiation of tumor cells (P = 0.014) in PLC, which is similar to previous findings with OSCC. [8].…”
Section: Discussionsupporting
confidence: 87%
“…Although women generally live longer than men,38 there were no sex effects for recurrence or survival. Two‐year recurrence and survival rates were similar to those found in other studies 39, 40. The median serum IL‐6 level of the sample was 13 pg/mL (range, 0 pg/mL‐453 pg/mL), which was lower than the mean of 19.5 pg/mL (range, 0 pg/mL ‐313 pg/mL) found in a smaller sample (N = 90) of HNSCC patients 7.…”
Section: Discussionsupporting
confidence: 85%